Pengaruh Variasi Arus terhadap Struktur Mikro, Kekerasandan Kekuatan Sambungan pada Proses PengelasanAlumunium dengan Metode SMAW - Dermawan, Nazar Arif; , Tri Widodo Besar Riyadi ST, MS.c, ph.D (2016)
This study aims to determine the chemical composition, microstructure, hardness and tensile tests on metals used in SMAW welding and also to determine the effect of current used on the quality of the weld. In this study researched the strength of the weld joint in the 6015 series aluminum with strong variations in electric current in the welding process Shielded Metal Arc Welding (SMAW). Tensile test specimens all make use of standard ASTM E8, micro structural test using ASTM standard E3 and hardness tests using standard ASTM E92. Strong variations of current used is 70 A, 75 A, 80 A, 85 A and 90 A, with voltage of 20-30 V and a speed of 14-20 inches / min The results showed that; strong electric current has a significant effect on microstructure, hardness and tensile strength 6015 series aluminum welding connection with SMAW welding process.